2006
DOI: 10.1029/2006ja011839
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive enhancements of oxygen ions during substorms

Abstract: [1] It has been observed that H + is the dominant ion species in the plasma sheet and the ring current during quiet times. However, the O + /H + density ratio increases with increasing geomagnetic storm and substorm activity. Energetic neutral atom (ENA) images from Imager for Magnetopause-to-Aurora Global Exploration/High Energy Neutral Atom (IMAGE/HENA) reveal the rapid increase of O + ring current at substorm expansion. Finding the cause of this substorm-associated O + enhancement is the main focus of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
141
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(152 citation statements)
references
References 52 publications
10
141
1
Order By: Relevance
“…Figure 38(a) shows an example (Frank 1970). A simulation study of an imaged ring current shows also that the ring current belt was located between 3 and 7 L during a moderate storm (Fok et al 2006). Thus, there is an indication that the substorm intensity depends on the location of the accumulated energy, as well as the power ε.…”
Section: Storm Intensity and The Location Of The Energy Accumulationmentioning
confidence: 99%
“…Figure 38(a) shows an example (Frank 1970). A simulation study of an imaged ring current shows also that the ring current belt was located between 3 and 7 L during a moderate storm (Fok et al 2006). Thus, there is an indication that the substorm intensity depends on the location of the accumulated energy, as well as the power ε.…”
Section: Storm Intensity and The Location Of The Energy Accumulationmentioning
confidence: 99%
“…It has been suggested that the ionospheric origin of low-energy O + ions in the lobe/plasma sheet are strongly accelerated at the magnetic reconnection region (X = −20 to −30 R E ), and are subsequently transported into the nearEarth plasma sheet Wilken et al, 1995;Zong et al, 1997Zong et al, , 1998]. Also proposed is that the energization of O + ions is caused by substorm-associated magnetic field reconfiguration and/or current sheet acceleration [Delcourt et al, 1990;Sánchez et al, 1993;Nosé et al, 2000;Fok et al, 2006;Nosé et al, 2009]. However, it was argued by Daglis and Axford [1996] that there existed a direct short-timescale feeding of the magnetosphere with ionospheric ions, indicating the injection of O + ions to the ring current region was faster than the traditional concepts as described in the paper by Kamide et al [1998].…”
Section: Introductionmentioning
confidence: 99%
“…Ionospheric plasma is highly collisional, and the plasma above ∼500 km is essentially collisionless. It has been recently realized that for a successful description of such a plasma system, a complex solution is needed which allows different physics domains to be described using different physical models (De Zeeuw et al, 2004;Fok et al, 2006;Moore et al, 2008;Ridley et al, 2004;Tóth et al, 2005;Tóth et al, 2011;Zhang, Liemohn, De Zeeuw, Borovsky, Ridley, Toth, Sazykin, Thomsen, Kozyra, Gombosi & Wolf, 2007). This is the reason why coupled models are intensively developed and improved during recent years.…”
Section: Discussion and Directions For Future Workmentioning
confidence: 99%